2023
DOI: 10.12659/ajcr.938359
|View full text |Cite
|
Sign up to set email alerts
|

A 64-Year-Old Man Hospitalized for COVID-19 Pneumonia and Treated with Tocilizumab Who Developed Chronic Cavitary Pulmonary Aspergillosis

Abstract: Rare coexistence of disease or pathology Background:The management of (Coronavirus disease 2019) COVID-19 pneumonia is ever-evolving. Tocilizumab, a monoclonal antibody against interleukin-6 (IL-6) receptor, have known mortality benefit in severe COVID-19 pneumonia, but data are limited regarding safety. Attributable to the immunomodulatory nature of this medication, patients may be at risk for opportunistic infections, including chronic cavitary pulmonary aspergillosis (CPPA), a slowly progressive disease cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
(49 reference statements)
0
1
0
Order By: Relevance
“…The most superinfections found were ventilator-associated pneumonia caused by Staphylococcus aureus in about 50% of cases. In the literature, there have been reports of candidemia and invasive pulmonary aspergillosis occurring in patients who were treated with TZB ( 43 , 44 ). In our study cohort, bacteriemia was found in 20 (16.53%) patients, with Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%
“…The most superinfections found were ventilator-associated pneumonia caused by Staphylococcus aureus in about 50% of cases. In the literature, there have been reports of candidemia and invasive pulmonary aspergillosis occurring in patients who were treated with TZB ( 43 , 44 ). In our study cohort, bacteriemia was found in 20 (16.53%) patients, with Acinetobacter spp.…”
Section: Discussionmentioning
confidence: 99%